MAIN FACTORS OF UNSECCESSFULL AVIATION PROJECTS - Ozturk, Serdar (My University, 2012)
The aim of this dissertation is to understand what aviation projects are and which factors affect their success. In getting more global and competitive world, aviation sector and project managing dramatically change and getting more complex. Because of end-user expectations and competiveness necessitate, aviation projects have to be completed within desired objectives. Thus, this study has been prepared in order to understand how to fulfill project’s necessities and to answer research questions (What are aviation projects and their properties? Which factors affect aviation projects goals? And who thinks what about these factors? And what are the key factors to be successful for aviation projects?). When this study was prepared; last developments, methods and current aviation projects were considered. In this study, firstly literature and development of project management have been overviewed. Secondly aviation project identifications, components, phases and properties have been determined with previous studies. Thirdly performance indicator concepts and success criteria have been assessed from different aspects. Fourthly, using BCFI methods, case company and compering other studies; aviation projects have deeply analyzed. And the last part of this dissertation has been concluded under previous studies and analysis. End of this study, it have been reached that depend on project types, properties, attributes and/or factors can affect to aviation project results. Moreover, not only aviation project but also all kind of projects are unique and each of them should be assessed in its own conditions.
Keywords: Aviation projects; projects components; success criteria; reasons for unsuccessful projects; critical factors for projects.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|